Plant genetic resources and traditional knowledge for food security - Salgotra, Romesh Kumar; Gupta, Bharat Bhushan (Springer, 2015)
With exponentially increasing population across the globe and shrinking resources, the concern of food security is looming large over the world community. To catch up with the fierce pace of growth in all the sectors of development, ensuring uninhibited availability of food resources is a prime agenda. The growing global demand for food, feed, fiber and bio-based renewable materials, such as bio-fuels, is changing the conditions for genetic resources development and bio-resource production worldwide. The crucial role in ensuring food security is played by the agro-based industries and enterprises. Advances in plant genetic resources coupled with traditional knowledge of the local tribes and native practices facilitate achievement of food security.